Catchment Area Treatment Plan for Directly Draining Sub-watersheds of Sardar Sarovar Catchment (Maharashtra) Using Remotely Sensed Data - Kimothi, M. M.; Jadhav, R. N.; Kandya, A. K.; Mankare, M. B.; Bhalekar, P. B.; Chavan, S. G. (Indian Forester, 1996)
Sardar Sarovar Project (SSP) is multistate multipurpose river valley which is expected to benefit and aid in development of four states namely Gujarat, Madhya Pradesh, Maharashtra and Rajasthan. The catchment area of Narmada river above Sardar Sarovar Dam, is 88.000 km2 of which 1676 km2 area is part of Maharashtra State. The area is predominantly forested and tribal in nature and social and economic life of the people is totally dependent on forest for food, fuel, fodder, timber and medicines. This needs for up-to-date and reliable information on current status of land utilization for important planning processes such as catchment area treatment (CAT). At the instance of Maharashtra Forest Department a detailed microlevel catchment area treatment package was evolved using remotely sensed satellite data (IRS-LISS II and SPOT) and the recommendation for five categories of CAT has been made to preserve forest and biodiversity in the catchment area along with development of tribal community by way of massive afforestation programme coupled with soil and water conservation. Five years phasing of CAT plan with annual target of 20% area under various treatments have been recommended. The total cost of the CAT plan has been worked out around 2801.40 lakhs with an employment generation of 64.39 lakhs man days. Based on this CAT plan using remotely sensed data the implementation of the CAT has been started from Oct, 1993 with an opening of four new Watershed Management Division by the Maharashtra Forest Department.